Communication about environmental health risks: A systematic review - Ciliska Donna; Yost Jennifer; Fitzpatrick-Lewis Donna; Krishnaratne Shari (BMC, 2010)
Abstract Background Using the most effective methods and techniques for communicating risk to the public is critical. Understanding the impact that different types of risk communication have played in real and perceived public health risks can provide information about how messages, policies and programs can and should be communicated in order to be most effective. The purpose of this systematic review is to identify the effectiveness of communication strategies and factors that impact communication uptake related to environmental health risks. Methods A systematic review of English articles using multiple databases with appropriate search terms. Data sources also included grey literature. Key organization websites and key journals were hand searched for relevant articles. Consultation with experts took place to locate any additional references. Articles had to meet relevance criteria for study design [randomized controlled trials, clinical controlled trials, cohort analytic, cohort, any pre-post, interrupted time series, mixed methods or any qualitative studies), participants (those in community-living, non-clinical populations), interventions (including, but not limited to, any community-based methods or tools such as Internet, telephone, media-based interventions or any combination thereof), and outcomes (reported measurable outcomes such as awareness, knowledge or attitudinal or behavioural change). Articles were assessed for quality and data was extracted using standardized tools by two independent reviewers. Articles were given an overall assessment of strong, moderate or weak quality. Results There were no strong or moderate studies. Meta-analysis was not appropriate to the data. Data for 24 articles were analyzed and reported in a narrative format. The findings suggest that a multi-media approach is more effective than any single media approach. Similarly, printed material that offers a combination of information types (i.e., text and diagrams) is a more effective than just a single type, such as all text. Findings also suggest that factors influencing response to risk communications are impacted by personal risk perception, previous personal experience with risk, sources of information and trust in those sources. Conclusions No single method of message delivery is best. Risk communication strategies that incorporate the needs of the target audience(s) with a multi-faceted delivery method are most effective at reaching the audience.